Layanan Aplikasi Ojek Online Maxim bagi Siswa MAN 4 Kota Pekanbaru - Rara Dita Anggraini; Dian Ayunia Rabbani; Elly Nielwaty (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the effectiveness of Maxim online motorcycle taxi services for students of MAN 4 Pekanbaru City in meeting their daily mobility needs. The location of MAN 4 Pekanbaru City on Jalan Yos Sudarso, one of the routes with a fairly high intensity of large vehicle activity, demands the availability of transportation services that can provide certainty of time, comfort, and safety for students. In this context, the existence of online motorcycle taxis is a relevant transportation alternative in today's digital era. This study uses a descriptive qualitative approach with the aim of describing in depth the experiences, perceptions, and assessments of students' assessments of the quality of Maxim online motorcycle taxi services. Data collection techniques were carried out through interviews with several students of MAN 4 Pekanbaru City who actively use the service in their daily activities, especially for going to and from school. The results of the study indicate that Maxim online motorcycle taxi services are considered quite effective in supporting student mobility, especially in terms of ease of access, time efficiency, and relatively affordable costs compared to other modes of transportation. In addition, the use of digital-based applications provides ease in ordering and transparency of fares. However, the aspects of safety and comfort remain a primary concern for students. Therefore, it is recommended that students use official online motorcycle taxi (ojek) applications to minimize the risk of fraud and other undesirable incidents. Overall, the Maxim online motorcycle taxi service serves as a transportation solution that supports students' mobility needs in urban environments.